Kepercayaan Tradisional Masyarakat Jawa dalam Novel Suti Karya Sapardi Djoko Damono: Kajian Sosiologi Sastra - Yulianti, Eva; Nama, I Ketut (Humanis, 2018)
I choose the novel Suti as the research object because firstly, in this novel it is described about historical ocassion in the year of 1960’s. Second, the novel Suti has a rural background. Third, the novel Suti describes the belief that had happened in the rural region. There are two problems that will be discussed. First, structure analysis that consists og figures, plots, and background. Second, literature sociology discussion that consists of javanese traditional belief. There are two results oh this research, they are structure analysis and literature sociology analysis that discuss about javanese traditional belief in the novel Suti. The main character in this novel is Suti. Besides, there are secondary and complementary characters too. The plots in this novel are divided into three plots. The first plot tells about the life of Suti since little until adult. The second plot tells about the close relationship between Suti and Sastro’s family, until finally Suti disappers by being brought away by her mother. The last plot tells about the life of Sastro’s family after being left by Suti, until finally Suti went back to Tungkal Village. The background in this novel are divided into three backgrounds, they are background pf place that takes place in Tungkal Village, Solo, Jakarta, and Yogyakarta. Background of time that describes the situation in the year of 1960’s, and background of culture that tells about the daily life of Tungkal Village’s people, ranging from traditional rituals until behaviors. The analysis of traditional belief in the novel Suti uses the theory of Wayland. D. Hand, that the traditional belief is divided into four aspects, such as : (1)  the belief in the environment of human’s life, for example the beliefs about weton, age of marriage, etc; (2) the belief about mystical world, for example the belief in the existence of Mbah Parmin and worshipping practice towards Mbah Parmin; (3) the belief in the creation of universe, for example the belief in the sound of crow; (4) the other kind of belief, for example someone’s behavior.